Increased Short-Term Beat-to-Beat QT Interval Variability in Patients with Impaired Glucose Tolerance - Orosz, Andrea; Baczkó, István; Nyiraty, Szabolcs; Körei, Anna E.; Putz, Zsuzsanna; Takács, Róbert; Nemes, Attila; Várkonyi, Tamás T.; Balogh, László; Ábrahám, György; Kempler, Péter; Papp, Julius Gy.; et al. (Frontiers in Endocrinology, 2017)
Prediabetic states and diabetes are important risk factors for cardiovascular morbidity and mortality. Determination of short-term QT interval variability (STVQT) is a non-invasive method for assessment of proarrhythmic risk. The aim of the study was to evaluate the STVQT in patients with impaired glucose tolerance (IGT). 18 IGT patients (age: 63±11 years, BMI: 31±6 kg/m2, fasting glucose: 6.0±0.4 mmol/l, 120 min postload glucose: 9.0±1.0 mmol/l, HbA1c: 5.9±0.4%; mean±SD) and 18 healthy controls (age: 56±9 years, BMI: 27±5 kg/m2, fasting glucose: 5.2±0.4 mmol/l, 120 min postload glucose: 5.5±1.3 mmol/l, HbA1c: 5.4±0.3%) were enrolled into the study. ECGs were recorded, processed, and analyzed off-line. The RR and QT intervals were expressed as the average of 30 consecutive beats, the temporal instability of beat-to-beat repolarization was characterized by calculating STVQT as follows: STVQT = ∑|QTn+1-QTn| (30x√2)-1. Autonomic function was assessed by means of standard cardiovascular reflex tests. There were no differences between IGT and control groups in QT (411±43 ms vs 402±39 ms) and QTc (431±25 ms vs 424±19 ms) intervals or QT dispersion (44±13 ms vs 42±17 ms). However, STVQT was significantly higher in IGT patients (5.0±0.7 ms vs 3.7±0.7, P<0.0001). The elevated temporal STVQT in patients with IGT may be an early indicator of increased instability of cardiac repolarization during prediabetic conditions.